Determinants of switching intention in the electricity markets - An integrated structural model approach. (November 2022) - Hussain, Shahid; Seet, Pi-Shen; Ryan, Maria; Iranmanesh, Mohammad; Cripps, Helen; Salam, Abdul
Abstract: This study adopts an integrated approach and combines the theory of planned behavior and push-pull theory to unpack the antecedents of customer switching intention in a contextual setting (Western Australia) that has a regulated electricity market. Partial least squares structural equation modeling was used to analyze data from a survey of 405 retail electricity consumers, which reveals that perceived relative price, electronic word-of-mouth, customer-based reputation of a service provider, past switching experience, and subjective norms significantly influence attitude toward switching and switching intention. Our findings contribute to the literature on retail electricity markets by showing the importance of customer-based reputation and positive electronic word-of-mouth in shaping consumers' attitude and intention toward switching their electricity providers. The results also provide insights for electricity retailers to design better offerings and control customer switching.